α-MnO 2 activation of peroxymonosulfate for catalytic phenol degradation in aqueous solutions - Saputra, Edy; Muhammad, Syaifullah; Sun, Hongqi; Patel, A.; Shukla, P.; Zhu, Z.; Wang, Shaobin (Elsevier Science, 2012)
Several α-MnO2 catalysts in the forms of nanosphere, nanorod and nanowire were synthesized, characterized and tested in heterogeneous activation of peroxymonosulfate for phenol degradation in aqueous solutions. The α-MnO2 materials exhibited varying activities in activation of peroxymonosulfate to produce sulfate radicals for phenol degradation depending on structure and morphology. Crystalline structure of MnO2 is more important than porous structure in influencing the activity because crystalline α-MnO2 exhibited higher phenol degradation. Nanowired α-MnO2 presented the highest activity with stable performance while the mesoporous α-MnO2 nanosphere with amorphous structure presented the lowest activity and stability. Kinetic study showed that phenol degradation on α-MnO2 followed the first order kinetics.